Neutron reflectivity of an adsorbed water-soluble block copolymer at the air/water interface: The effects of pH and ionic strength - An, S; Thomas, R; Baines, F; Billingham, N; Armes, S; Penfold, J (1998)
We describe the effects of pH and added electrolyte on the structure of layers of poly(2-(dimethylamino)-ethyl methacrylate-block-methyl methacrylate) copolymer (poly(DMAEMA-b-MMA)) (70 mol % DMAEMA, Mn = 10 000) adsorbed at the air/water interface. Previously, we had shown by means of neutron reflection measurements that at a pH of 7.5 there is a surface phase transition from a layer about 20 Å thick to one about 40 Å thick and that the adsorbed layer at the higher concentration has a cross sectional structure resembling that expected for a micelle. The present work shows that the "micellar" structure is promoted by any changes in the solution that enhance the surface coverage but is inhibited by an increase in the fractional charge on the polyelectrolyte part of the copolymer. Some surprising lack of correlation between surface tension and surface coverages is also observed, which may be related to this unusual surface structure.